Kajian Etnosains Pembuatan Makanan Tradisional Lomak Daerah Manggarai - Wae, Veronika P. Sinta Mbia; Fatima, Noviana Deam; Ndang, Yustika Elviani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to examine the ethnoscientific values contained in the process of making traditional Lomak food from the Manggarai area, East Nusa Tenggara. Lomak is one of the culinary heritage that not only has a distinctive taste, but also reflects the local knowledge of the Manggarai people, starting from the selection of ingredients, processing techniques, to food preservation efforts. This study uses a qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation studies. The results of the study show that the process of making Lomak contains scientific principles, such as natural fermentation techniques, sustainable use of local ingredients, and traditional knowledge about sanitation and food conservation. This ethnoscience study is expected to be a source of contextual learning in science education while contributing to the preservation of local culture. The novelty of this research lies in the application of food innovation that combines aspects of business management, marketing strategy, and cultural preservation, so that it has the potential to increase the income of Lomak artisans in the Manggarai area.